Front Cover: A C4N4 Diaminopyrimidine Fluorophore (Chem. Eur. J. 17/2019). Issue 17 (4th March 2019) - Noda, Hidetoshi; Asada, Yasuko; Maruyama, Tatsuro; Takizawa, Naoki; Noda, Nobuo N.; Shibasaki, Masakatsu; Kumagai, Naoya
Abstract : A new scaffold for producing efficient organic fluorescent materials was identified: 2, 5‐diamino‐1, 3‐diarylpyrimidine featuring a C4N4 elemental composition. Single‐step installation of two aryl groups at the 4, 6‐positions of the pyrimidine core delivered fluorescent organic materials in a modular fashion. A variety of fluorescent compounds with distinct absorption/emission properties was readily accessed in a modular fashion by varying the peripheral aromatic attachments. This cover picture visualizes the central C4N4 core efficiently harvesting light to intensely emit fluorescence in a range of wavelengths. More information can be found in the Communication by M. Shibasaki, N. Kumagai, et al. onpage 4299 .